Answer: The required factored form of the given expression is
![(x^4y^6+1)(x^8y^{12}-x^4y^6+1).](https://tex.z-dn.net/?f=%28x%5E4y%5E6%2B1%29%28x%5E8y%5E%7B12%7D-x%5E4y%5E6%2B1%29.)
Step-by-step explanation: We are given to find the factored form of the following algebraic expression:
![E=x^{12}y^{18}+1.](https://tex.z-dn.net/?f=E%3Dx%5E%7B12%7Dy%5E%7B18%7D%2B1.)
We will be using the following formula:
![a^3+b^3=(a+b)(a^2+ab+b^2).](https://tex.z-dn.net/?f=a%5E3%2Bb%5E3%3D%28a%2Bb%29%28a%5E2%2Bab%2Bb%5E2%29.)
Now, we have
![E\\\\=x^{12}y^{18}+1\\\\=(x^4y^6)^3+1^3\\\\=(x^4y^6+1)\{(x^4y^6)^2-x^4y^6\times1+1^2\}\\\\=(x^4y^6+1)(x^8y^{12}-x^4y^6+1).](https://tex.z-dn.net/?f=E%5C%5C%5C%5C%3Dx%5E%7B12%7Dy%5E%7B18%7D%2B1%5C%5C%5C%5C%3D%28x%5E4y%5E6%29%5E3%2B1%5E3%5C%5C%5C%5C%3D%28x%5E4y%5E6%2B1%29%5C%7B%28x%5E4y%5E6%29%5E2-x%5E4y%5E6%5Ctimes1%2B1%5E2%5C%7D%5C%5C%5C%5C%3D%28x%5E4y%5E6%2B1%29%28x%5E8y%5E%7B12%7D-x%5E4y%5E6%2B1%29.)
Thus, the required factored form of the given expression is
![(x^4y^6+1)(x^8y^{12}-x^4y^6+1).](https://tex.z-dn.net/?f=%28x%5E4y%5E6%2B1%29%28x%5E8y%5E%7B12%7D-x%5E4y%5E6%2B1%29.)
Answer:
growth = 2 x day
^growth based off what day it is
^how much it grows per day
^ day at hand
2x14 (2 weeks)= 28 cm
?
Answer:
11.4
Step-by-step explanation:
Answer:
25
Step-by-step explanation:
25 is the y intercept.